IMPLEMENTASI KEBIJAKAN POLRI TERHADAP PELAKU PENGGUNA SABU-SABU DI BAWAH 1 GRAM (Studi Pada Wilayah Hukum Kepolisian Resor Kota Bandar Lampung) - Bambang Hartono (Unissula, 2012)
Imprisonment is not the only way out of the actions for the perpetrator who use drugs and psychotropic, there is other way which can be passed by rehabilitation. The executant and distributor have different position which has to know. The executant is victim who should be rehabilitated, while distributor is criminal who should be in prison. The problems of this research is how the police policy toward the perpetrator of Heroin less than 1 gram.The research method which is used in this thesis is normative and empirical approach. Secondary data is obtained from any document or literature, and this approach is supported by three (3) legal materials, namely: primary legal materials, secondary and tertiary.According to the result, it can be concluded that the police provides policies to Heroin user less than 1 gram, but it bases on several considerations. It includes as follows: narcotic sand psychotropic perpetrator who is still under age at the first time caught and forced by someone, the evidence of heroin less than 1 gram, if the child is using heroin. Policy which is given by police toward the perpetrators of heroin under 1 gram consists of rehabilitation policy and the separation policy between users and distributor of narcotic sand psychotropic confinementKeywords : Implementation, Police, Heroi